Development Of E-Document Information System In Information And Computer Engineering Department Using Quick Response Code - Suhartono Suhartono; Ristin Susilawati Zahraen (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
Development of an E-Document Information System in the Department of Informatics and Computer Engineering using a QR Code. Informatics and Computer Engineering Education Study Program. Department of Informatics and Computer Engineering. Faculty of Engineering. Makassar public university. This study aims to develop an E-Document mailing information system using Quick Response Code. This research is a type of Research Development (RD) research. The development of this system is carried out using the RAD development method or model. Other methods used include direct observation, interviews with related parties, and questionnaires or questionnaires to determine the feasibility of the aspects of their use. The research subjects in the development of this system are staff and students of the Department of Informatics and Computer Engineering. The results of software testing based on the ISO 25010 testing standard showed that the functional suitability aspect was in the very good category, the performance efficiency aspect of the results obtained by the GTMatrix class obtained a C value with 68% performance, the structure was 85% by obtaining 2.6 seconds and was included in the very category. well, the portability aspect is in the very good category or has a value of 1, which means that the system test on the device being tested is successful because it can be run in different browser types. The Usability aspect got a presentation result of 87.6% so that the score was included in the very feasible category, and these results indicate that this system meets the Usability aspect category.